DIGITALIZATION OF ISLAMIC ACCOUNTING LEARNING AT IAIN BONE ACCOUNTING LABORATORY: PERSPECTIVE ON UTILITARIANISM THEORY - Masyhuri; Widya Astuti; A Adryan Hidayat (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
This Research aims to develop Islamic accounting learning media through the perspective of digitalization-based utilitarianism theory as part of digital transformation. Media developed by utilizing social media accounting laboratory IAIN Bone. This research is a Research and Development (R&D) research with an orientation to develop a research product. Research starts from needs analysis, planning, product development, expert validation, and revision. To measure its effectiveness, limited field tests are used. The results of this study conclude the availability of learning media for the subject of Islamic accounting material that has been tested for effectiveness based on utilitarianism theory which is useful as celebrity digital content and received a positive response from students. The implication of this research is to be an input to educators and laboratories to be sensitive and able to optimize digitalization of learning as an accountable and useful digital transformation effort.